Evaluation of Some Trace Elements Pollution in Sediments of the Tigris River in Wasit Governorate, Iraq - Issa et al. (مجلة بغداد للعلوم, 2020)
The main objectives of present study are to evaluate the trace elements pollution in the sediment of the Tigris River and drainage canals in Wasit Governorate, Iraq. Assessment of trace elements pollutants were conducted for 18 sediment samples collected in March 2017. Trace elements were analyzed in sediment Tigris River samples in Wasit Governorate. This metal pollution was evaluated using geo-accumulation (I-geo) index, Contamination Factor (CF) and Pollution Load Index (PLI). According to  these statistical indices, the sediments collected from Tigris River in the study area are highly polluted with Titanium (71.9 ppm), Nickel (226.6 ppm) Chromium (425.2 ppm), Cadmium (2ppm) and Molybdenum (15.8 ppm) while  the sediments  were moderately polluted with Cobalt (25.1 ppm), Strontium (839.3 ppm), Copper (56.2), Manganese (106.1ppm), Vanadium (135 ppm), Niobium (9.79 ppm). However, the sediments of the Tigris River is not polluted by Lead, Barium, Gallium, Rubidium and, Zinc.  Metals concentration levels in the sediments of the drainage canals that discharged into the Tigris River showed higher concentrations  than  the Tigris sediments in Ta, V, Ni, Cu, Ga, Br, Sr and Mo.